Perencanaan Strategis SI/TI Dalam Meningkatkan Kualitas Pelayanan Pasien : Studi Kasus RS XYZ - Aditiyawijaya, Hendra; Harya Damar Widiputra (The Indonesian Journal of Computer Science, 2025)
Advances in information systems and information technology (IS/IT) have become an important element in improving the quality of health services. XYZ Jakarta Hospital faces challenges in integrating IS/IT to support health services to patients. This research aims to develop an IT strategic plan that is in line with the hospital's business objectives, using the IASA IT Strategic Planning methodology. The results showed that although XYZ Hospital has various information systems, their investment and implementation have not been fully integrated with the hospital's business processes. The resulting recommendations include strengthening infrastructure, improving system interoperability, and efficient patient data management. With the right strategy, it is expected that IS/IT can contribute to improving service quality and patient trust in a sustainable manner.